Encapsulation of Pharmaceutical and Nutraceutical Active Ingredients Using Electrospinning Processes - Mina Zare; Karolina Dziemidowicz; Gareth R. Williams; Seeram Ramakrishna (Nanomaterials, 2021)
Electrospinning is an inexpensive and powerful method that employs a polymer solution and strong electric field to produce nanofibers. These can be applied in diverse biological and medical applications. Due to their large surface area, controllable surface functionalization and properties, and typically high biocompatibility electrospun nanofibers are recognized as promising materials for the manufacturing of drug delivery systems. Electrospinning offers the potential to formulate poorly soluble drugs as amorphous solid dispersions to improve solubility, bioavailability and targeting of drug release. It is also a successful strategy for the encapsulation of nutraceuticals. This review aims to briefly discuss the concept of electrospinning and recent progress in manufacturing electrospun drug delivery systems. It will further consider in detail the encapsulation of nutraceuticals, particularly probiotics.